2015
DOI: 10.1074/jbc.m115.644336
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Caveolin-induced Membrane Curvature

Abstract: Background: Caveolin-1 (Cav1) requires the caveolin scaffolding domain for caveola formation. Results: The Cav1 scaffolding domain and oligomerization domain are tightly juxtaposed to the membrane in caveolae. Conclusion: Concerted membrane association of the oligomerization, scaffolding, and intramembrane domains are critical for caveola biogenesis and membrane deformation. Significance: Understanding the membrane association of Cav1 is critical for dissecting how the protein regulates caveola formation and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
127
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(141 citation statements)
references
References 56 publications
14
127
0
Order By: Relevance
“…Finally, cryoEM tomography of caveolae in situ suggested that rather than being purely spherical, caveola bulbs possess inherent polygonal symmetries. Interestingly, identical polygonal symmetry is observed by cryoEM in a model system in which CAV1 alone drives formation of caveolalike vesicles in bacterial membranes (13). This finding strongly suggests that CAV1 is responsible for this polygonal architecture, rather than the peripheral cavin coat, although in mammalian cells both components are required to form a stable caveola.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Finally, cryoEM tomography of caveolae in situ suggested that rather than being purely spherical, caveola bulbs possess inherent polygonal symmetries. Interestingly, identical polygonal symmetry is observed by cryoEM in a model system in which CAV1 alone drives formation of caveolalike vesicles in bacterial membranes (13). This finding strongly suggests that CAV1 is responsible for this polygonal architecture, rather than the peripheral cavin coat, although in mammalian cells both components are required to form a stable caveola.…”
supporting
confidence: 61%
“…Studies by many laboratories in recent years are now beginning to bridge this gulf using approaches that include biochemical isolation, NMR spectroscopy, EM, and X-ray crystallography (6,10,(12)(13)(14)(15)(16)(17). A picture is now emerging of a vesicular structure that possesses much greater complexity than originally thought.…”
mentioning
confidence: 99%
“…Analysis of the reconstituted Cavin1 vesicles indicated that the Cavin1 coat alone can cause such polygonal shapes. In this context it is interesting that, when expressed in bacteria in the absence of cavins, caveolin generates vesicles of similar size and shape (34,35). Thus, the polygonal shape of caveolae is probably favored, generated, and maintained by both caveolins and cavins.…”
Section: Discussionmentioning
confidence: 99%
“…From a structural standpoint, Cav1 contains a hairpin loop structure, three palmitoylation sites, and a scaffolding domain that facilitates interaction with the PM (12). The scaffolding domain of Cav1 (amino acids 82-101) contains three cationic residues that bind to the negatively charged headgroups of PtdSer and PtdIns(4,5)P 2 via electrostatic interactions (13,14).These in vitro studies revealed that PtdIns(4,5)P 2 is the preferred ligand on a per mole basis.…”
Section: Edited By Dennis R Voelkermentioning
confidence: 99%